PROFESSOR M. S. SPIROV − TALANTED SCIENTIST, INSOLVABLE PERSON - Кузьменко Ю. Ю.; Маліков О. В. (World of Medicine and Biology, 2018)
The article highlights the life and creative ways, as well as the pedagogical activity of Mikhail Sergeyevich Spirov, a well-known teacher, professor, head of the human anatomy department of the Kiev Medical Institute more than 40 years. Life and scientific and pedagogical activities M. S. Spirov serves as a vivid example of diligence, a sense of responsibility and duty, dedication to science. Professor Spirov − one of the organizers of the modern Kiev anatomical school, his creative qualities and organizational skills inspired to further development.